Analysis of Regional Regulations Related to the Implementation of Regulations for Substituting Building Permits in Bantul Regency - Vicki Dwi Purnomo; Benedictus Hestu Cipto Handoyo; Syukron Abdul Kadir (Jurnal Pengabdian Masyarakat Formosa, 2022)
One of the affairs that falls under the authority of the regional government of Bantul Regency is related to the affairs of the Implementation of Building Construction which is then regulated through Regional Regulation No. 3 of 2022 concerning Implementation of Building Construction. Regional regulations as written laws made based on the needs of the community must of course be adapted to societal developments and the legal politics of government administration. Therefore regional regulations require periodic evaluations to see the suitability of the regulated content material with developments in implementation in the community. This research focuses on what is the urgency of analysis and evaluation of Bantul Regency Regional Regulation No. 3 of 2022 concerning Implementation of Buildings, and how to analyze and evaluate the Bantul Regency Regional Regulation No. 3 of 2022 concerning Organization of Buildings. The research was carried out using the juridical-normative method with the laws and regulations approach, which was then analyzed descriptively qualitatively. The research found that both formally and materially the content was in accordance with the sectoral law, namely Law Number 28 of 2002 and further provisions stipulated in PP No. 16 of 2021 concerning Regulations for Implementing Law Number 28 of 2002 concerning Buildings, but it seems that it is only a copy and paste of the two legal bases. For this reason, in order to avoid repetition or duplication of arrangements, it is necessary to make arrangements that take into account local needs and wisdom in Bantul.